Inverkan av utfodringsnivå och miljö på reproduktion och hållbarhet hos rekryteringskvigor - Johansson, Lisbeth (2008)
This study is based on an earlier interdisciplinary study made by Redbo et al., (2000), Extensive cattle production systems – out wintering, which lasted over two winters, 97/98 and 98/99, with two groups of heifers indoors and two groups of heifers outdoors raised in different environments, indoors or outdoors during their second winter. Both indoor and outdoor heifer groups were fed grass silage ad libitum throughout the experimental period that lasted from October until May. The objective of this study was to evaluate the long term effects of being raised in these two environments. This study includes data collected during the period lasting from the start of the experiment of Redbo et al., (2000) until the heifers had calved a second time and the results mainly deal with the performance of the animals after the experiment during their first two calvings and their first lactation. The effects of earlier environment on a number of traits such as reproduction, leg- and hoof health, sustainability and production ability were studied.